Pengembangan Aplikasi Pembelajaran untuk Mendukung Mahasiswa dalam Belajar Pemrograman Java berbasis Android (Studi Kasus : FILKOM UB) - Fadhyl Farhan Alghifari; Komang Candra Brata; Ahmad Afif Supianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The advancement of information technology in Indonesia have resulted IT Graduated Students are necessarily needed. However, there are still many graduates who are considered disappointing. One of the factors causing this problem is the exlcusion of programming curricula at the elementary, junior, and senior high school level and the limited access to programming course. Then, the authors collected data by questionnaire to 58 students of the Faculty of Computer Science Universitas Brawijaya (FILKOM UB) in 2018 where 75.9% of respondents thought that learning programming on mobile devices would make it easier for them to learn programming because it would facilitate access to learning. Then, 91.4% of respondents never learned the Java Language before becoming a college student, even though Java is a programming language that is often used. Therefore, the M-Learning application to learn Java Programming is necessary to facilitate students in learning Java Programming. This research will use the Mobile-D method in which the M-Learning application is flexible and the Mobile-D method is used because it can adapt to the users need. Based on the results of research conducted, user ratings of applications with an average SUS score of 84 for students and 70 for lecturers, it can be concluded that Java-Based Learning Applications to Support Students in Learning Java Programming are easy to use and can be accepted by users.